Pesan Moral dalam Film KKN di Desa Penari: Analisis Semiotika Roland Barthes - Nur Laila; Ahmad Zulfikar Ali (Fakultas Dakwah Institut Dirosat Islamiyah Al-Amien Prenduan, 2026)
With increasingly sophisticated technology and the ability to present everything, it has led to moral decline. Without us realizing it, a moral crisis is currently affecting young people, especially teenagers, in this era. One effort to prevent this moral decline is utilizing mass communication media in the form of film. One such film,